Peningkatan Kualitas Sumber Daya Manusia Melalui Pelatihan Peranan Humas bagi Anggota Polresta Tangerang - Heriyanti, Heriyanti; Ummanah, Ummanah; Tambunan, Resman Maharul (LPkM Universitas Bakrie, 2021)
The rapid technology development and information made public (community) being so critical to the policies was taken by the government. This requires police institution to maintain of security guards, public order, enforce the law, provides protection, aegis and service to the community. Public Relations (PR) is an agency which have a duty to understand and evaluate a variety of public opinion in order to help to create harmony between particular agencies with the public. In order to increase quality of human resources in Police Department are required personnel with the ability in resolving problems the happens in society. In resolving these problems, that needed cooperation between police department, college and the community. The contribution of college to police department and the community with conducting the devotion to the community in cooperation Polresta Tangerang. The method in use in devotion community is by providing training of the role of public relations to Polresta Tangerang members through zoom cloud meeting. The role of public relations training aimed at giving public knowledge include similarity in communication, public relations function, basic principles of public relations, the management of the community and management of media relations may be good quality police. The evaluation of the training be concluded that the training that performed capable of increase understanding participants on the role of public relations.